Gender, cultural influences, and coping with musculoskeleta pain at work - Ismail Maakip; Jodi Oakman; Rwth Stuckey (Springer New York LLC, 2017)
Purpose Workers with musculoskeletal pain (MSP) often continue to work despite their condition. Understanding the factors that enable them to remain at work provides insights into the development of appropriate workplace accommodations. This qualitative study aims to explore the strategies utilised by female Malaysian office workers with MSP to maintain productive employment. Methods A qualitative approach using thematic analysis was used. Individual semi-structured interviews were conducted with 13 female Malaysian office workers with MSP. Initial codes were identified and refined through iterative discussion to further develop the emerging codes and modify the coding framework. A further stage of coding was undertaken to eliminate redundant codes and establish analytic connections between distinct themes. Results Two major themes were identified: managing the demands of work and maintaining employment with persistent musculoskeletal pain. Participants reported developing strategies to assist them to remain at work, but most focused on individually initiated adaptations or peer support, rather than systemic changes to work systems or practices. A combination of the patriarchal and hierarchical cultural occupational context emerged as a critical factor in the finding of individual or peer based adaptations rather than organizational accommodations. Conclusions It is recommended that supervisors be educated in the benefits of maintaining and retaining employees with MSP, and encouraged to challenge cultural norms and develop appropriate flexible workplace accommodations through consultation and negotiation with these workers.